Differences in Student Learning Outcomes Using Problem-Based Learning and Discovery Learning to Teach Arithmetic Sequences and Series - Febrily Pangemanan; Rosiah J. Pulukadang; Jorry F. Monoarfa (Departement of Mathematics Education, 2023)
This study compares the learning outcomes of students at SMA Negeri 2 Tondano using the Problem-Based Learning and Discovery Learning models to teach arithmetic sequences and series. This study employs a quasi-experimental design to conduct experimental research. This research was conducted on two classes. The data collection technique employs a test technique in which the validity of the test being tested is determined. Examine the hypothesis using the t-test, after ensuring normality and homogeneity. The results revealed that the Problem-Based Learning model produced average learning outcomes of 80.97, while the Discovery Learning model produced average learning outcomes of 75.18. Based on the t-test results tcount = 1.905 > ttable = t((0.05:57)) = 1.672, it can be concluded that the average student learning outcomes taught using the Problem-Based Learning model are greater than those taught using the Discovery Learning model.